The effect of bio-banding on physical and psychological indicators of talent identification in academy soccer players. Issue 4 (2nd October 2021) - Towlson, Christopher; MacMaster, Calum; Gonçalves, Bruno; Sampaio, Jaime; Toner, John; MacFarlane, Niall; Barrett, Steve; Hamilton, Ally; Jack, Rory; Hunter, Frances; Myers, Tony; Abt, Grant
ABSTRACT: The aim of this study was to examine the effect of bio-banding on indicators of talent identification in academy soccer players. Seventy-two 11 to 14-year-old soccer players were bio-banded using percentage of estimated adult stature attainment (week 1), maturity-offset (week 2) or a mixed-maturity method (week 3). Players contested five maturity (mis)matched small-sided games with physical and psychological determinants measured. Data were analysed using a series of Bayesian hierarchical models, fitted with different response distributions and different random and fixed effect structures. Few between-maturity differences existed for physical measures. Pre - peak height velocity (PHV) and post-PHV players differed in PlayerLoad TM (anterior-posterior and medial-lateral) having effect sizes above our criterion value. Estimated adult stature attainment explained more of the variance in eight of the physical variables and showed the greatest individual differences between maturity groups across all psychological variables. Pre-PHV and post-PHV players differed in positive attitude, confidence, competitiveness, total psychological score (effect sizes = 0.43–0.69), and session rating of perceived exertion. The maturity-offset method outperformed the estimated adult stature attainment method in all psychological variables. Maturity-matched bio-banding had limited effect on physical variables across all players while enhancing a number of psychological variables considered key for talent identification in pre-PHV players.